Hands-on learning! more than 1000 activities for young children using everyday objects - Kaltman, Gwen Snyder (Corwin Press, 2009)
From the Publisher: Organized into 16 themes, this resource features more than 1,000 hands-on activities using inexpensive, readily available objects to engage young children's senses.